Nowatorstwo czy false start? : pierwsze omnibusy konne we Wrocławiu - Sielicki, Tomasz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
The following article introduces the beginnings of public transport in Wrocław, dating back to 1840, when, thanks to Conrad Kißling and Julius Lange, first regular horse-drawn omnibus lines were launched – first to towns on the outskirts of Wrocław, and then in inner city center.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne